SEMANTIC AND SYNTACTIC FEATURES OF OBJECTS IN ENGLISH AND VIETNAMESE - ĐẶNG THỊ THỦY (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
In both English and Vietnamese, object with various aspects in its syntax and semantics is considered one of basic constituents of the clause. This study is designed to yield an explicit analysis from which the features of objects have been drawn syntactically and semantically. It comes from the study that objects in English and Vietnamese, apart from the similarities, reveal quite many differences which are regarded as language barriers for the learners and the chief cause of errors made by Vietnamese learners of English in using sentences including objects. Accordingly, some suggestions to the language teaching and learning have been offered in the hope that Vietnamese learners of English can get great benefit from the study.